Mid-trimester maternal serum placental growth factor (PLGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) combined with fetal Doppler studies in prediction of preeclampsia. (2022)
Background: There have been many studies on prediction of preeclampsia but there is no single test which has demonstrated sufficient predictive value. Combination of maternal biomarkers with fetal Doppler studies are the promising predictors. Objective: The purpose of this study was to evaluate midtrimester maternal serum PLGF, sFlt-1 and fetal Doppler studies in predicting preeclampsia. Methodology: This is a cohort study of 120 consenting pregnant women between the gestational ages of 18–24weeks had blood sample collected for PLGF and sFlt-1and Doppler obstetrics Ultrasound scan was performed at recruitment. The women were followed up longitudinally throughout pregnancy. Standard statistics methods were adopted as applicable. The level of statistical significance was set at 5% (P-value <0.05). Results: A total of 115 participants had complete data for analysis and 16 (13.9%) developed preeclampsia. There was a statistically significant difference in the serum level of sFlt-1 and the sFlt-1/PLGF in those that developed preeclampsia with P-values of 0.009 and 0.014 respectively. There was a significant statistical difference in those with abnormal uterine artery PI and RI, Umbilical artery PI and RI among those that developed preeclampsia. Combining sFlt-1 and sFlt-1/PLGF with uterine and umbilical arteries PI and RI on Receiver operating characteristics (ROC) curve yielded an Area under the curve (AUC) of 0.925 with a sensitivity of 93.8% at a specificity of 65.7%. Conclusion: The combination of the serum PLGF, sFlt-1 and fetal doppler in the midtrimester had highest sensitivity in predicting preeclampsia compared to when they are used singly, and this will form a valuable tool in predicting preeclampsia in those presenting late in second trimester.